Serra de São Mamede Natural Park, a macrofungal diversity hotspot in the Mediterranean region - Santos-Silva, Celeste (2022)
The Serra de São Mamede Natural Park is a biodiversity hotspot in the broad region of Alentejo, Portugal, where the influence of the Atlantic Ocean allows for the continuity of a Eurosiberian-like forest in the heart of a Mediterranean region. The park is therefore unique among the few protected areas in Portugal. We attempt to describe the macrofungal diversity of the park for the first time. Our results reveal a rich and diverse assembly of macrofungal species (239 taxa), and in particular, mycorrhizal species (145 taxa). Furthermore, 26 taxa are newly recorded from Portugal, while 81 taxa are newly recorded from Alto Alentejo Province. Also, the majority of these newly reported taxa were recorded in mixed stands of Quercus pyrenaica Willd.—a European protected habitat of limited extent—whose importance is enhanced now the rich and diverse associated macrofungal community, as shown in our study.